Determinants of residential property prices in Germany: Evidence from a structural approach - Florian Kajuth (Verein für Socialpolitik, 2010)
We use a GMM approach to estimate the impact of standard macroeconomic variables on house prices in Germany. In order to avoid interpolation of house price data we use annual data and look separately at the demand and supply side. Our findings suggest that nominal and real house prices in Germany are reasonably well explained by disposable income, population growth, construction costs and to a lesser extent by nominal interest rates.
Keywords: R21; R31; E21; 330; Residential property prices; GMM; housing demand and supply